Zooplanktons As Bioindicators Of Water Pollution From Vikram Tearth Sarovar Ujjain (M.P) (Journal of Pharmaceutical Negative Results, 2022)
Freshwater ecosystems harbor a vast diversity of Zooplanktons, and such diverse taxonomic groups play important roles in ecosystemfunctioning and services. Bioindicators are living organisms such as plants, planktons, animals, and microbes, which are utilized toscreen the health of the natural ecosystem in the environment. They are used for assessing environmental health and biogeographicchanges taking place in the environment. Each organic entity inside a biological system provides an indication regarding the health ofits surroundings such as zooplankton responding rapidly to changes taking place in the surrounding environment and serving as animportant biomarker for assessing the quality of water as well as an indicator of water pollution. Some species of Zooplanktons aresensitive to water quality oscillations from natural or anthropogenic causes. Information on basic ecological attributes such asabundance or absence can be helpful in the context of hydric resource monitoring. In the present study Zooplankton communitiesfrom Vikram Tearth Sarovar (Ujjain) of Madhya Pradesh (India) were sampled from (Jan. 2018- Dec.2018) in order to ascertain thetrophic status of these freshwater bodies of Madhya Pradesh using Zooplankton as indicators. The present study discussesBrachionus: Trichocerca ratio for the evaluation of the nature of the recognized Site. Our aim was to identify and understand theabundance of species with potential to monitor water quality in large scale assessments. The selected water body suggested that therewas a tremendous anthropogenic pressure on the freshwater bodies of Madhya Pradesh. Different species of plankters have wide aswell as narrow range of tolerance towards the fluctuating environmental conditions. It can be inferred from the study that the VikramTearth Sarovar is under the tremendous pressures of anthropogenic activities as was reflected by high B/T values. During the presentstudy a total of 53 taxa of zooplankton comprising 24 Rotifers, 15 Cladocerans, 12 Copepods and only 2 Ostracods were found toinhabit the Vikram Tearth Sarovar. The presence of organic pollution indicators Brachionus calyciflorus, Keretella Tropica, Keretellapriodonta, Chydorous Sphaericus, Moina sp, Lapdella patella, B. caudatus, B.falactus, Asplanchana brightweli, Asplanchanapriodonta, Ceriodaphnia reticulate, Ceriodaphnia sps. etc. is a warning sign of the deteriorating condition of the water quality in thereservoir. Measures need to be enforced to reduce the rate of pollution of the selected water body arising from the human activities inthe catchment of the reservoir.